KINERJA GURU BAHASA JEPANG SMA SE-KOTA PEKANBARU SEBAGAI IMPLEMENTASI KURIKULUM 2013 PADA PROSES PEMBELAJARAN - Sadam Husin; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is aimed to determine the performance of Japanese language teachers of SMA in Pekanbaru as the implementation ofCurriculum2013 in the process of learning based on the perception of Japanese teachers and the school. Respondents in this study were 7 Japanese language teachers and 4 representatives of the school curriculum. Sampling technique used in this this research was Saturated Sampling. This technique used in order to determine the sample when all members of the population used as the sample. The data were collected through observation, questionnaires, interviews and documentation. The research method used was descriptive quantitative. This method was done by processing data and presented through percentage calculation and the answer. Based on the results of the study, it can be concluded that the overall data on the performance of Japanese teachers based on the perception of teachers were in good category (51% -100%), with a percentage of 59.4%. The data obtained about the performance of Japanese teacher of SMA in Pekanbaru as the implementation of Curriculum 2013 in the learning process based on the perception of the school were in good category (51% -100%), with the acquisition of percentage was equal to 68,7%. Further researchers are expected to involve students to be part of this study.Key Words: Curriculum 2013, Teachers’ Perfomance